2015
DOI: 10.1007/s00402-015-2313-8
|View full text |Cite
|
Sign up to set email alerts
|

Cephalomedullary nails: factors associated with impingement of the anterior cortex of the femur in a Hispanic population

Abstract: Posterior entry site should be avoided and an anterior site should be used. Female gender, straight nails and greater angle of incidence of the femur were associated with cortical impingement. A specific intramedullary nail design is needed for the Hispanic population due to high impingement and anterior cortical penetration rates seen with conventional nails. Short curved nails and long nails with a lower radius of curvature are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…7) [36]. But, one thing should be paid attention: the curvature of anterolateral femoral bowing is usually increased in the elderly, which may lead to the mismatching between the cephalomedullary nail and the femur and cause cortical impingement and tail protrusion [37][38][39][40]. For these patients, we performed the following procedures to prevent these complications: 1) using the long main nail; 2) the nail entry point should be selected anterior, but not posterior to the greater trochanter; and 3) when the excellent PSA of the guide pin was achieved by rotation of the main nail, the traction force can be slightly elevated.…”
Section: Discussionmentioning
confidence: 99%
“…7) [36]. But, one thing should be paid attention: the curvature of anterolateral femoral bowing is usually increased in the elderly, which may lead to the mismatching between the cephalomedullary nail and the femur and cause cortical impingement and tail protrusion [37][38][39][40]. For these patients, we performed the following procedures to prevent these complications: 1) using the long main nail; 2) the nail entry point should be selected anterior, but not posterior to the greater trochanter; and 3) when the excellent PSA of the guide pin was achieved by rotation of the main nail, the traction force can be slightly elevated.…”
Section: Discussionmentioning
confidence: 99%
“…Peña et al 9 found that the posterior nail start site was an incidental factor related with cortical impingement. Roberts et al 8 believed that the posterior entry point increases the angle at which the nail is inserted, leading to over contact between the nail and the anterior cortex of the femur.…”
Section: Discussionmentioning
confidence: 99%
“…6 As one of the common complications, cortical impingement caused by the over contact of the tip of the nail and the femoral cortex may often lead to thigh pain and even fractures of the femoral shaft, which seriously affect postoperative rehabilitation and limb function of patients. 7,9 Previous studies have reported a higher incidence in the Asian population, 10 which may be attributed to the differences of bone morphology and mismatch of implant. As it is well known, Asian femurs are smaller than Caucasian and have a larger anterior bow.…”
Section: Introductionmentioning
confidence: 99%
“…Nails are designed to be placed in the medullary canal of the femur, but because of a variety of problems (such as entry point errors, osteoporosis, and radius of curvature mismatch between the femur and nail) the nail can abut against or perforate the cortex of the femur distally [2]. Abutment or perforation can cause pain or secondary fracture [4, 6]. The problem of nail abutment or penetration also occurs with femoral shaft fractures but is much less common because these patients are different from those with proximal femur fractures.…”
Section: Where Are We Now?mentioning
confidence: 99%
“…Abutment or perforation can cause pain or secondary fracture [4,6]. The problem of nail abutment or penetration also occurs with femoral shaft fractures but is much less common because these patients are different from those with proximal femur fractures.…”
mentioning
confidence: 99%